A atudy on the atylistic features and teaching strategy of Kuo Pao Kuns Chinese expressionist drama Kopi Diam and The Silly Little Girl and the Funny Old Tree - Li, Zhengjun (Tanjong Malim, 2020)
A atudy on the atylistic features and teaching strategy of Kuo Pao Kuns Chinese expressionist drama Kopi Diam and The Silly Little Girl and the Funny Old Tree by Li, Zhengjun